Peran Madrasah Baitul Mu’minin di Desa Ngemplak dalam Membentuk Akhlaq Generasi Alpha Berbasis Qur’anic Empowerment - Dade’ Nur Baeti; Salis Irvan Fuadi; Salma Zulala; Safani Safani; Habib Hamidun; Putri Refi Mariska A. (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Madrasahs play a strategic role in shaping the moral character of young generations amid the challenges of the digital era, particularly Generation Alpha, who grow up in an environment dominated by technology. This community service activity aims to analyze and strengthen the role of Madrasah Baitul Mu’minin in Ngemplak Village in forming the moral character (akhlaq) of Generation Alpha through a Qur’anic empowerment approach. This program employed a qualitative approach using a case study method. Data were collected through participatory observation, in-depth interviews, and documentation, involving madrasah caregivers, teachers (ustadz and ustadzah), students, and parents. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that Madrasah Baitul Mu’minin plays a significant role in strengthening the moral character of Generation Alpha through Qur’an-based learning that emphasizes understanding and value implementation, consistent religious habituation, and exemplary behavior of educators. The Qur’anic empowerment approach proved effective in internalizing Qur’anic values and fostering moral awareness among students. Furthermore, the madrasah functions as a moral and spiritual development center that helps counterbalance the negative impacts of digital technology. These findings highlight the importance of non-formal madrasahs as adaptive bases for Islamic character education in responding to contemporary challenges.